2014
DOI: 10.1016/j.bbamcr.2013.08.022
|View full text |Cite
|
Sign up to set email alerts
|

SUMO-targeted ubiquitin ligases

Abstract: Covalent posttranslational modification with SUMO (small ubiquitin-related modifier) modulates functions of a wide range of proteins in eukaryotic cells. Sumoylation affects the activity, interaction properties, subcellular localization and the stability of its substrate proteins. The recent discovery of a novel class of ubiquitin ligases (E3), termed ULS (E3-S) or STUbL, that recognize sumoylated proteins, links SUMO modification to the ubiquitin/proteasome system. Here we review recent insights into the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
238
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(245 citation statements)
references
References 163 publications
3
238
0
Order By: Relevance
“…The SUMOtargeted E3 ubiquitin ligase (STUbL) family of proteins mediates crosstalk between ubiquitin and SUMO. STUbL-dependent ubiquitination of SUMO conjugated target proteins, coupled or not with target degradation at the proteasome, drives key processes in the maintenance of genome stability [20][21][22][23]. The human STUbL RNF4 was recently demonstrated to act directly in DSB repair, by targeting multiple sumoylated proteins including MDC1, 53BP1 and BRCA1 [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The SUMOtargeted E3 ubiquitin ligase (STUbL) family of proteins mediates crosstalk between ubiquitin and SUMO. STUbL-dependent ubiquitination of SUMO conjugated target proteins, coupled or not with target degradation at the proteasome, drives key processes in the maintenance of genome stability [20][21][22][23]. The human STUbL RNF4 was recently demonstrated to act directly in DSB repair, by targeting multiple sumoylated proteins including MDC1, 53BP1 and BRCA1 [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Some viral proteins function as a SUMO E3 ligase, including the Ad5 E1B-55K protein (16,17) for p53 sumoylation and Kaposi's sarcoma-associated herpesvirus (KSHV) KbZIP (18) for sumoylation of p53 and the retinoblastoma protein. Recent studies have demonstrated that poly-SUMO2/3 chains serve as a ubiquitination signal for SUMO-targeted ubiquitin ligases (STUbLs) and proteasomal degradation (19). Mammalian STUbLs include RNF4 and RNF111 (Arkadia) and viral STUbLs include varicella zoster virus ORF61, herpes simplex virus-1 ICP0, and KSHV K-Rta (19,20).…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that poly-SUMO2/3 chains serve as a ubiquitination signal for SUMO-targeted ubiquitin ligases (STUbLs) and proteasomal degradation (19). Mammalian STUbLs include RNF4 and RNF111 (Arkadia) and viral STUbLs include varicella zoster virus ORF61, herpes simplex virus-1 ICP0, and KSHV K-Rta (19,20).…”
mentioning
confidence: 99%
“…In many cases, ubiquitylation by RNF4 leads to proteasomal degradation; for example, SUMO-dependent ubiquitylation by RNF4 leads to degradation of the promyelocytic leukemia (PML) protein and its related oncogenic fusion protein PML-RAR (a fusion between PML and the retinoic acid receptor a). Moreover, expression of RNF4 results in differentiation of PML-RAR leukemic cells, 6 suggesting that RNF4 functions as a tumor suppressor in promyelocytic leukemia. In contrast, in the case of epithelial cancers RNF4-dependent ubiquitylation potentiates the tumorigenic properties of cancer cells.…”
Section: Dysregulated Proteostasis In Cancermentioning
confidence: 99%
“…RNF4 stabilizing activity also requires its association with nucleosomes. A point mutation, K179D, that blocks this association prevents ubiquitylation, stabilization, and transcriptional enhancement, 5,6 suggesting that RNF4 acts on, or in the vicinity of, chromatin. Nevertheless, how atypical ubiquitylation and association with nucleosomes results in oncoprotein potentiation is not clear.…”
Section: Mechanisms Of Rnf4-dependent Stabilization and Oncogene Actimentioning
confidence: 99%